What does it take for flexible learning to survive? A UK case study. Issue 1 (19th September 2019) - Talbot, Jon; Perrin, David; Meakin, Bob
Abstract : Purpose: The purpose of this paper is to identify potential reasons for the success of an innovative work-based learning (WBL) shell framework in an adverse environment. Design/methodology/approach: Case study is the experience of one programme. Findings: Demand-led, flexible WBL programmes have to overcome a number of internal cultural and institutional barriers in order to succeed. Important requirements are likely to include effective leadership, financial viability, adherence to quality assurance, adaptability, entrepreneurialism and a cohesive community of practice incorporating these traits. Research limitations/implications: The conclusions are drawn from shared experience and are suggestive only as they are not readily susceptible to empirical verification. The authors accept that the conclusions appear speculative for some, but they suggest that in order for innovative programmes to survive, more is required than sound pedagogy. Practical implications: Although lessons may not be directly transferable, the paper draws attention to the importance of managerial, leadership and organisational factors necessary for innovative WBL programmes to survive and develop. Originality/value: There is some literature on why some innovative higher education programmes and institutions have failed; however, there is little on why some programmes are successful.